Health Promoting Behavior Among School Going Adolescents in Puducherry-A Cross-Sectional Study - Swaminathan, Sinthu Sarathamani; Boratne, Abhijit Vinodrao; Patil, Rajkumar; Sankaran, Avudaiappan (Indian Journal of Community Health, 2020)
Background: Health promotion is considered as a process that strengthens health conditions, shapes attitudes, supports behavioural changes to attain the utmost physical and mental health, and organizes the social and physical environment of a person. Aim & Objective: To identify the level of health-promoting behaviour and the associated socio-demographic factors among school-going adolescents in Puducherry. Settings and Design: A cross-sectional analytical study was conducted among 705 school-going adolescents of standard IX-XII from five government and private schools in rural and urban areas. Methods and Material: Multistage sampling was used to select the subjects and the Adolescent Health Promotion Score (AHP 40) was used to assess the health-promoting behaviour of an adolescent. The data was entered in MS Excel and analysed using SPSS v16. Statistical analysis used: Mean ± SD were used to summarize the Total Adolescent Health Promotion Score. Multiple linear regression model was used to assess the association between socio-demographic variables and Adolescent health promotion behaviour. Results: Among the 705 participants, the mean age of the students was 14.9 (±1.4). The mean AHP score of the students was 147.78(±20.59). It was observed that the majority of the students (53%) had a high health promoting behaviour. The number of siblings and father’s profession significantly predicted higher scores of adolescent health promoting behaviour. Conclusions: More than half of the student population had high level of health promoting behaviour. The family and school related variables had significant association with the health promoting behaviour of adolescents